United States - China Trade War Issue: Impact on Inflation and Indonesia’s Export Performance - Romauli Nainggolan; Benedecta Nadya Evangelie (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: The import tariffs imposed by the United States (U.S) on 10 countries have received mixed responses. Indonesia is subject to an import tariff of 32%—the highest in the history of international trade. Due to this condition, several countries have entered negotiations to request a reduction in import tariffs. Such negotiations are crucial because high import tariffs may weaken the economic growth of exporting countries and reduce their export value to the U.S.Purpose: To examine the impact of domestic macroeconomic factors and U.S. import tariff fluctuations on the long-term value of Indonesia’s fish exports.Design/methodology/approach: Autoregressive Distributed Lag (ARDL) analysis technique is applied in this explanatory quantitative research to test long-term relationships among variables. The data used are monthly time series data covering the period 2015–2024.Findings/Result: Short-term and long-term ARDL equations show that inflation and import tariffs significantly affect Indonesia’s fish export performance to the United States. In addition, a long-term complementary correlation was found between exports to China and exports to the U.S. For every 1% increase in fish exports to China, fish exports to the U.S. increase by about 0.41% within the following 21 months. This indicates the existence of common external demand, value chain integration, or global commodity conditions that influence both markets. This study provides important implications for fiscal and international trade policies. Fiscal authorities need to design strategies to maintain exchange rate and inflation stability.Conclusion: Indonesia’s domestic inflation, U.S.-imposed import tariffs, and Indonesia’s fish exports to China significantly influence the performance of Indonesia’s fish exports to the United States.Originality/value (State of the art): The object of study is the marine sector. Research on fish exports that compares two export destinations under conditions of high trade war tension is rare. In general, most studies only examine exports to a single destination country. Keywords: import tariff, United States, exchange rate, fish exports, Indonesia